Investment And Wage Policy As Drivers Of Economic Development In Java Island - Rozikin Rozikin; Herry Wira Wibawa; Donna Rahmiyanti; Arni Kurniati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Experts and the government have always been concerned about economic development in order to sustain and be able to make significant and high-quality contributions to the advancement of a better society. As the hub of Indonesia's economy and the island with the densest population, Java Island is crucial to the country's economy. This study aims to examine the possible impacts of investment and wage policies on Java Island's economic development using a quantitative descriptive-analytical approach research methodology. The results of the t and F test statistics confirm that foreign and local investment and wage policies contribute significantly to the Economic Development of Java Island. Foreign investment brings advantages in terms of technology and global market access, local investment plays an important role in strengthening the domestic economy. A balanced wage policy, linked to productivity, is important to ensure that the economic development generated by this investment is sustainable and inclusive.